The wave - Rhue, Morton (London : Heinemann, 1981)
A dramatization of an actual classroom experiment in establishing a fascist society. In this account, Laurie tries to persuade Mr. Ross to call off the experiment.
"This work is a novelization of a teleplay by Johnny Dawkins based on a short story by Ron Jones"--Verso t.p.
Booklist
School Library Journal
Young Adult
Young Adult
Keywords: Education -- Experimental methods -- Fiction; Fascism and youth -- Fiction